E-commerce and developing country-SME participation in global value chains - Rainer Lanz; Kathryn Lundquist; Grégoire Mansio; Andreas Maurer; Robert Teh (World Trade Organization (WTO), 2018)
Two far-reaching developments have increased the trade opportunities for SMEs in developing countries. Firstly, the rise of the internet and advances in ICT have reduced trade-related information and communication costs. Secondly, the international fragmentation of production has increased the opportunities for SMEs to specialize in narrow activities at various stages along the production chain. Using firm-level data from the World Bank's Enterprise Survey, we test whether digital connectivity, as captured by whether a firm has a website or not, facilitates the participation of manufacturing SMEs from developing countries in global value chains (GVCs). We find robust evidence that digital connectivity facilitates the participation of manufacturing SMEs in GVCs in terms of both backward and forward linkages. SMEs with a website tend to import a higher share of their inputs used for production and export a higher share of their sales as compared to SMEs without a website. Furthermore, the findings indicate that the effect of having a website on GVC participation is stronger for SMEs than for large firms. Beyond digital connectivity at the firm level, we also assess the role of a country's ICT infrastructure in facilitating GVC participation of SMEs. We find that SMEs tend to participate more in GVCs in countries where a higher share of the population has fixed broadband subscriptions. This result also holds if we control for other country-level factors such as the quality of logistics services, rule of law and access to finance. Our findings can provide guidance for policy makers in developing countries about the importance of investing in ICT infrastructure, creating a regulatory and policy environment conducive to e-commerce, and providing SMEs and workers with the digital skills and knowledge to use ICT technologies efficiently.
Keywords: F14; F63; 330; e-commerce; developing countries; small and medium-sized enterprises; global value chains